Species differences in hepatic biotransformation of the anthelmintic drug flubendazole - Maté, María Laura (2017)
Flubendazole (FLBZ) is a broad-spectrum benzimidazole anthelmintic used in pigs, poultry, and humans. It has been proposed as a candidate for development for use in elimination programmes for lymphatic filariasis and onchocerciasis in humans. Moreover, FLBZ has shown promise in cancer chemotherapy, particularly for neuroblastoma. This work investigated the hepatic carbonyl-reducing pathway of FLBZ in different species, including humans. Microsomal and cytosolic fractions were obtained from sheep, cattle, pig, hen, rat, and human liver. Both subcellular fractions of each species converted FLBZ into a reduced metabolite (red-FLBZ). The rate of microsomal red-FLBZ production was highest in sheep (1.92 ± 0.13 nmol/min.mg) and lowest in pigs (0.04 ± 0.02 nmol/min.mg); cytosolic red-FLBZ production ranged from 0.02 ± 0.01 (pig) to 1.86 ± 0.61 nmol/min.mg (sheep). Only subcellular fractions from sheep liver oxidized red-FLBZ to FLBZ in a NADP+-dependent oxidative reaction. Liver microsomes from both pigs and humans transformed FLBZ to red-FLBZ and a hydrolyzed metabolite. Very significant differences in the pattern of FLBZ metabolism were observed among the tested species and humans. These results reinforce the need for caution in extrapolating data on metabolism, efficacy, and safety of drugs derived from studies performed in different species.